Direct bisulphite conversion of cervical samples for DNA methylation analysis - Lisanne Verhoef; A. N Floore; Saskia Doorn; Kate Cuschieri; Ramya Bhatia; A. T Hesselink; Chris J.L.M. Meijer; Renske D.M. Steenbergen; Daniëlle A.M. Heideman (Epigenetics, 2022)
Sodium bisulphite conversion of DNA to separate methylated from unmethylated cytosines is a standard for methylation analysis. This study evaluated a direct cell conversion protocol on cervical samples as alternative to isolated genomic DNA as input. Clinician-collected cervical samples (n = 120) were subjected to a direct conversion protocol, or genomic DNA was isolated with a fixed amount used for subsequent bisulphite conversion. Converted samples were compared for ACTB control gene and methylation of FAM19A4 and miR124-2 genes using quantitative methylation-specific PCR (QIAsure Methylation Test). Direct conversion resulted in a high success rate, i.e., 119/120 (99.2%) samples reported a valid test result. ΔΔCq values of FAM19A4 and miR124-2 were significantly correlated between both protocols (Spearman Rho 0.708 and 0.763, respectively, all p-values = 0.000). Agreement between both the bisulphite protocols was demonstrated by Bland–Altman plots. A direct cell conversion protocol shows good technical and analytical performance and offers a streamlined workflow for methylation analysis.